2008
DOI: 10.1016/j.jcat.2008.10.007
|View full text |Cite
|
Sign up to set email alerts
|

How nitric oxide affects the decomposition of supported nickel nitrate to arrive at highly dispersed catalysts

Abstract: An explanation is put forward for the beneficial effect of thermal decomposition of supported Ni 3 (NO 3 ) 2 (OH) 4 in NO/He flow (0.1-1 vol%) that enables preparation of well-dispersed (3-5 nm particles) 24 wt% Ni-catalysts via impregnation and drying using aqueous [Ni(OH 2 ) 6 ](NO 3 ) 2 precursor solution. Moreover, combining electron tomography, XRD and N 2 -physisorption with SBA-15 support yielded a clear picture of the impact of air, He and NO/He gas atmospheres on NiO shape and distribution. TGA/MS ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
73
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 57 publications
(79 reference statements)
13
73
1
1
Order By: Relevance
“…Indeed, Table S2 (see the Supporting Information) shows that decomposition of cobalt nitrate in diluted NO at 240 8C results in smaller cobalt oxide particles, which is consistent both with our in situ EXAFS data ( Figure S7, the Supporting Information) and with previous reports by de Jong et al [9][10][11] Moreover, in contrast with Co-A C H T U N G T R E N N U N G (NO 3 ) 2 , nitrate ions, present in substoichiometry with respect to cobalt in hydroxynitrates, participate in the oxidation of cobalt and no dioxygen is produced during decomposition (compare Equations 2, 5 and 6). The brutal release of dioxygen has been reported to be detrimental to nickel oxide dispersion.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Indeed, Table S2 (see the Supporting Information) shows that decomposition of cobalt nitrate in diluted NO at 240 8C results in smaller cobalt oxide particles, which is consistent both with our in situ EXAFS data ( Figure S7, the Supporting Information) and with previous reports by de Jong et al [9][10][11] Moreover, in contrast with Co-A C H T U N G T R E N N U N G (NO 3 ) 2 , nitrate ions, present in substoichiometry with respect to cobalt in hydroxynitrates, participate in the oxidation of cobalt and no dioxygen is produced during decomposition (compare Equations 2, 5 and 6). The brutal release of dioxygen has been reported to be detrimental to nickel oxide dispersion.…”
supporting
confidence: 92%
“…This can be achieved by optimizing catalyst texture, [3] adding organic compounds, [4] [5] or promoters [6] during catalyst preparation, decomposing cobalt nitrate in a glow discharge [7] or by controlling the catalyst thermal activation. [8,9,10,11] In particular, de Jong et al prepared smaller Co 3 O 4 and Co 0 particles on SBA-15 silicas by activating the catalyst in a NO-containing atmosphere instead of air prior to the reduction. [9,10,11] In the present paper, in situ quick X-ray absorption spectroscopy (QXAS) has been used as a unique tool to accurately monitor the transformations of dispersed phases in supported catalysts under different atmospheres (air, helium and 5 % NO/He), both from the structural, quantitative, and kinetic standpoints.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3b). The first peak is due to the decomposition of the Ni nitrate precursor to Ni in its oxidized state [30][31][32][33] while the second peak is attributed to the reduction of nickel oxide species to metallic Ni [34]. For monometallic Cu sample, the reduction peak between 500 and 550 K (Fig.…”
Section: Tprmentioning
confidence: 99%
“…24, 29 We have previously reported that agglomeration of cobalt and nickel nitrate can effectively be prevented by replacing traditional air calcination with thermal treatment in 1% (v/v) NO/He flow, resulting in high NiO and Co 3 O 4 dispersions. 30,31 For silicasupported copper nitrate, it was reported that the drying step is of vital importance to the particle size distribution. 5 Drying at elevated temperatures resulted in agglomeration during the hydrolysis of copper nitrate hydrate to copper hydroxynitrate.…”
Section: ' Introductionmentioning
confidence: 99%